ON THE QUESTION OF THE ORGANIZATION OF THE EDUCATIONAL PROCESS IN THE CONDITIONS OF THE COVID-19 PANDEMIC - Давиденко, О.М.; Мироник, О.В. (SWorldJournal, 2023)
The work deals with the organization of the educational process in the conditions of the COVID-19 pandemic. Issues of advantages and disadvantages of various forms of education are discussed. Distance education is not an alternative, but only one of the a